2012
DOI: 10.1016/j.yqres.2012.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Re-evaluating the origins of late Pleistocene fire areas on Santa Rosa Island, California, USA

Abstract: At the close of the Pleistocene, fire regimes in North America changed significantly in response to climate change, megafaunal extinctions, anthropogenic burning and possibly, even an extraterrestrial impact. On California's Channel Islands, researchers have long debated the nature of late Pleistocene “fire areas,” discrete red zones in sedimentary deposits, interpreted by some as prehistoric mammoth-roasting pits created by humans. Further research found no evidence that these red zones were cultural in origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
(74 reference statements)
1
8
0
Order By: Relevance
“…The alluvial sediments in Arlington Canyon also contain numerous burned zones dating to the Pleistocene, as described above. Their presence, along with abundant charcoal dating to before the arrival of humans to the Channel Islands, underscores the findings of other researchers that fires represented in the sedimentary record of SRI and other Channel Islands were a part of natural cycles, rather than caused by humans (Johnson, ; Scott et al , ; Rick et al , ; Pigati et al , ; Hardiman et al , ). Additionally, the presence of charcoal in Pleistocene sediments and its relative absence in Holocene sediments likely reflects the change from a forested to a dominantly grassland environment (Anderson et al , ; Hardiman et al , ; Scott et al , ).…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…The alluvial sediments in Arlington Canyon also contain numerous burned zones dating to the Pleistocene, as described above. Their presence, along with abundant charcoal dating to before the arrival of humans to the Channel Islands, underscores the findings of other researchers that fires represented in the sedimentary record of SRI and other Channel Islands were a part of natural cycles, rather than caused by humans (Johnson, ; Scott et al , ; Rick et al , ; Pigati et al , ; Hardiman et al , ). Additionally, the presence of charcoal in Pleistocene sediments and its relative absence in Holocene sediments likely reflects the change from a forested to a dominantly grassland environment (Anderson et al , ; Hardiman et al , ; Scott et al , ).…”
Section: Resultssupporting
confidence: 52%
“…Quaternary Sci., Vol. 34(7) 499-508 (2019) the sedimentary record of SRI and other Channel Islands were a part of natural cycles, rather than caused by humans (Johnson, 1977;Scott et al, 2011;Rick et al, 2012;Pigati et al, 2014;Hardiman et al, 2016). Additionally, the presence of charcoal in Pleistocene sediments and its relative absence in Holocene sediments likely reflects the change from a forested to a dominantly grassland environment (Anderson et al, 2010;Hardiman et al, 2016;Scott et al, 2017).…”
Section: Implications For Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Wendorf (1982) reached the same conclusion shortly after Don conducted his research. A carefully conducted recent study that combined detailed stratigraphy, radiocarbon dating, paleobotany, and clay mineralogy reached the same conclusions about the fire areas on Santa Rosa Island (Rick et al 2012). Anderson et al (2010) reported evidence of Native American burning on Santa Rosa Island which increased in the late Holocene.…”
Section: Fire As a Factor In Landscape Historymentioning
confidence: 73%
“…Phil Orr argued that ancient peoples hunted mammoths, then cooked and processed them in mammoth fire‐roasting pits, some of which may have been 40,000 or more years old . These roasting pits or “fire areas” left reddish soil stains, some containing animal bones and other materials, which were later determined to be the result of either natural wildfires that burned through an area, or less likely staining from groundwater processes . Although the anthropogenic origins of the fire areas did not stand the test of time, more recent studies suggest that human‐induced burning may have increased during the Late Holocene, particularly after about 4,000 years ago on the Channel Islands .…”
Section: Forest Fires and Native American Burningmentioning
confidence: 99%